REGIONAL MECHANISM OF INTERNATIONAL COOPERATION IN THE FIELD OF COMBATING CRIME (Western European Journal of Historical Events and Social Science, 2025)
The article analyzes regional mechanisms of international cooperation in the field of combating crime. All conventions, treaties and agreements have been studied by the implementation of special procedural actions, which determine the international cooperation in criminal cases between contracting parties